User satisfaction on web based system: a case study of V.O.I.S.S system at UNITAR - Kadir, Badrul Hisyam (2004)
This paper describes study, which explored level of user satisfaction, the relationship of factor that influence satisfaction on Virtual Online Instruction Support System (VOISS) and provide some recommendation for education institutions interest on implement web based system. Five component of end user computing satisfaction (EUCS) that has been established in the literature are measured. The study was undertaken among students and lecturers from three faculties at UNIT AR Kelana Jaya campus. The finding reveal that, five components of end user computing satisfaction are positive association with user satisfaction on VOISS system and most of the user are in medium and high level of satisfaction. However, demographic profile such as sex, race, age, occupation and major had no effect on satisfaction. From the findings of this research, gives guidance for any institutions on future development of web based system to concern on five components of EUCS to fulfill the user satisfaction.